Evaluating genetic diversity and seed composition stability within Pan-African Soybean Variety Trials - de Meyer, M.; Prenger, E.; Mahmood, A.; da Fonseca Santos, M; Chigeza, G.; Song, O.; Mwadzingeni, L.; Mukoro, R.; Chibanda, M.; Mabuyaye, G.; Diers, B.; Scaboo, A. (2024)
Given high animal protein costs, protein deficiency is a prevalent form of malnutrition in sub‐Saharan Africa (SSA). Soybean [Glycine max (L.) Merr.] can provide a cheaper high‐quality protein source and fortify lysine‐limited cereal‐based diets. Breeding soybean for seed composition in SSA requires understanding genotype by environment interactions (G × E). African breeding programs submit cultivars for evaluation in the Pan‐African Soybean Variety Trials (PATs), providing the opportunity to examine G × E across diverse environments. With PAT data, we conducted additive main effects and multiplicative interaction (AMMI) and genotype plus genotype‐by‐environment (GGE) biplot analyses on seed protein and oil content of 17 cultivars grown with two replications in nine environments across Zimbabwe. Across environments, protein ranged from 322.8 to 445.1 g kg−1 and oil ranged from 164.8 to 242.7 g kg−1. For protein AMMI analysis, MAKWACHA performed best for both stability and a combination of stability plus content. For oil AMMI analysis, SC SPIKE performed best for stability and KALEYA performed best for a combination of stability plus content. GGE biplot analyses identified three different mega‐environments for protein and oil, with SC EXPT2, KALEYA, and SC EXPT1 having highest protein content and TGX 2002‐9FM, LUKANGA, and SC EXPT3 having highest oil content. We also evaluated genetic diversity of 19 PAT cultivars through phylogenetic analyses with 1059 USDA Germplasm Resources Information Network (GRIN) diversity panel accessions. We recommend stable and adaptable PAT cultivars to breeders and producers while highlighting genetically distinct accessions with valuable traits as a resource for breeding programs.